A Continuous Seismostratigraphic Framework for the Western Svalbard-Barents Sea Margin Over the Last 2.7 Ma: Implications for the Late Cenozoic Glacial History of the Svalbard-Barents Sea Ice Sheet - Alexandropoulou, Nikolitsa; Winsborrow, Monica; Andreassen, Karin; Plaza-Faverola, Andreia; Dessandier, Pierre-Antoine; Mattingsdal, Rune; Baeten, Nicole; Knies, Jochen (Frontiers in Earth Science, 2021)
Here we present a high-resolution, continuous seismostratigraphic framework that for the first time, connects the over 1000 km long western Svalbard-Barents Sea margin and covers the last 2.7 million years (Ma). By exploiting recent improvements in chronology, we establish a set of reliable age fix-points from available boreholes along the margin. We then use a large 2-D seismic database to extend this consistent chronology from the Yermak Plateau and offshore western Svalbard, southwards to the Bear Island Trough-Mouth Fan. Based on this new stratigraphic framework we divide the seismic stratigraphy along the continental margin into three seismic units, and twelve regionally correlated seismic reflections, each with an estimated age assignment. We demonstrate one potential application of this framework by reconstructing the Svalbard-Barents Sea Ice Sheet evolution from the intensification of the northern hemisphere glaciation at 2.7 Ma to the Weichselian glaciations. Through seismic facies distribution and sedimentation rate fluctuations along the margin we distinguish three phases of glacial development. The higher temporal resolution provided by this new framework, allows us to document a clear two-step onset to glacial intensification in the region during phase 1, between 2.7 and 1.5 Ma. The initial step, between 2.7 and 2.58 Ma shows glacial expansion across Svalbard. The first indication of shelf-edge glaciation is on the Sjubrebanken Trough-Mouth Fan, northwestern Barents Sea after 2.58 Ma; whilst the second step, between 1.95 and 1.78 Ma shows glacial advances beyond Svalbard to the northwestern Barents Sea. Phase 2 is characterized by variations in sedimentation rates and the seismic facies are indicative for a regional glacial intensification for the whole Barents Sea-Svalbard region with widespread shelf-edge glaciations recorded at around 1.5 Ma. During Phase 3, the western Barents Sea margin is characterized by a dramatic increase in sedimentation rates, inferring once again a regional glacial intensification. Our new stratigraphic framework allows for the first time differentiation of the sediments deposited on the slope during Early Saalian ( 0.4 and 0.2 Ma), Late Saalian ( 0.2 and 0.13 Ma) and Weichselian (< 0.123 Ma) periods, providing new insights into the Barents Sea glaciations over the last 0.42 Ma.